100 questions & answers about peripheral artery disease (PAD) - Mohler, Emile R.; Hirsch, Alan T. (Alan Tick) (Sudbury, Mass. : Jones and Bartlett Publishers, 2010)
'What is Pad? What are the symptoms of PAD? Is there a cure for PAD? When might I need an angioplasty? How do I gain control over my life now that I have PAD?' -- Cover, p.1.
Keywords: Arterial Occlusive Diseases -- Popular Works; Peripheral Vascular Diseases -- Popular Works